Perception-based Supplier Attributes and Performance Implications: A Multimethod Exploratory Study - Thomas Clauss; Chanchai Tangpong (Journal of Supply Chain Management, 2019)
Attributes of suppliers such as capabilities are considered important aspects of successful buyer–supplier relationships. Previous research relates supplier attributes largely to intraorganizational supply chain practices, such as supplier selection and evaluation, and assumes that supplier attributes can be objectively assessed independently of the relationships with suppliers. This study expands on this literature by (1) exploring supplier attributes as perceived by purchasing managers in ongoing buyer–supplier relationships and (2) examining how these perception-based supplier attributes are associated with performance-influencing practices, which can in turn shape relational outcomes of the relationships. In doing so, we combine two exploratory qualitative studies. We conduct 60 repertory grid interviews with purchasing managers in Study 1 and 25 semi-structured interviews with another set of purchasing managers in Study 2. The findings of this study are finally theorized through the supply chain practice view and are summarized into an integrative theoretical model. This study thus provides a more nuanced understanding of perception-based supplier attributes and their implications on performance-influencing practices and relational outcomes in buyer–supplier relationships.
Keywords: 330; buyer; supplier relationships; supplier evaluation; buyer perceptions; supplier attributes; relational performance; dark side of buyer; supplier relationships; supply chain practice view; repertory grid technique; semi-structured interviews